Role of infectious disease information system and risk assessment in control of livestock diseases in Indian perspectives: A review - SURESH, K P; PATIL, S S; YASASWINI, L; HEMADRI, D; DESAI, G S; RAHMAN, H (The Indian Journal of Animal Sciences, 2017)
Many livestock diseases have a severe impact on the country’s economic status. Diseases cause highly destructive epidemics. It imposes severe consequences, especially in the areas of densely populated livestock. Infectious Disease Informatics, an emerging field of study, involves information management in a systematic way and analysis of issues related to infectious disease detection, prevention and management. Surveillance and awareness are the two essential phenomenon to be adapted, so that the early detection of disease outbreaks is possible and rapid control measures are schemed to prevent further spread of the disease. Recent advances in disease surveillance system, information technology and epidemiological modelling have raised the expectations on the early warning systems as they are not only sensible but also necessary tools to combat the re-occurrence and spread of infectious diseases. The evolution of remote sensing instrumentation, GIS technology and their application and evaluation of satellite data to the issues of disease risk prediction are reviewed and discussed. The importance of risk assessment and disease risk prediction in livestock epidemiology has been illustrated with example case studies. An overview of the types of epidemiological studies, various sampling techniques and the role of meta-analysis in livestock disease informatics has been specified. The paper also focuses on the techniques being developed for infectious disease risk prediction in both space and time.